Barbarossa the first 7 days - Fowler, Will (Casemate, 2004)
On 22 June 1941 The Germans launched their long-expected invasion of the Soviet Union. Codenamed ""Operation Barbarossa," after the famous 12th century crusading emperor, what followed was perhaps the greatest clash of arms the world has ever witnessed. With the aid of specially commissioned maps, Barbarossa: The First 7 Days describes the dramatic history of the first week of the invasion of the Soviet Union. The book begins with an extensive overview of the Wehrmacht's success up until 1941, followed by chapters outlining the German High Command's plan of attack and the defensive dispositions of the Soviet forces. The author goes on to describe the opening bombardment, followed by detailed accounts of the three Army Groups' fortunes in the first week of the campaign. The book finishes with an analysis of the remainder of the campaign and the ultimate failure of the Germans to destroy the Red Army and capture Moscow. With first hand accounts from both sides, vivid photographs, detailed fact boxes, and specially commissioned maps of the German advance and the Soviet defensive actions, Barbarossa: The First 7 Days is a comprehensive examination of the first week of the four-year war on the Eastern Front.